2020
DOI: 10.1002/er.5611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of assembling method and force on the performance of proton‐exchange membrane fuel cells with metal foam flow field

Abstract: Recently, highly porous metal foams have been used to replace the traditional open-flow channels to improve gas transport and distribution in the cells. Deformation of flow plate, gas diffusion layer (GDL), and metal foam may occur during assembling. When the cell size is small, the deformation may not be significant. For large area cells, the deformation may become significant to affect the cell performance. In this study, an assembling device that is capable of applying uniform clamping force is built to fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…They also found that a higher contact pressure is beneficial to heat conduction, improving the uniformity of the temperature field and avoiding local hot spots. Weng et al [24] studied the contact pressure between the metal BPP and GDL under different clamping forces. A polarization curve test and electrochemical spectrum (EIS) experiment were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that a higher contact pressure is beneficial to heat conduction, improving the uniformity of the temperature field and avoiding local hot spots. Weng et al [24] studied the contact pressure between the metal BPP and GDL under different clamping forces. A polarization curve test and electrochemical spectrum (EIS) experiment were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cell (PEMFC) has become one of the most studied and widely used fuel cells because of its small size, high power density and high energy conversion efficiency [1][2][3]. PEMFC is mainly composed of endplates, insulating plates, collector plates, bipolar plates and membrane electrodes assembly [4].…”
Section: Introductionmentioning
confidence: 99%
“…This thus reduces oxygen mass transport to reaction sites of the catalyst finally resulting in poor fuel cell power performance [13]. Accordingly, various technologies, including 3D mesh flow field plates [14,15], ordered structure electrodes [16] and hydrophobic GDLs [17], have been investigated to overcome the water management issues.…”
Section: Introductionmentioning
confidence: 99%